Untreated recurrent acute necrotising encephalopathy associated with Ran binding protein 2 mutation, and normal outcome in a Caucasian boy. (29th September 2015) - Loh, N-R; Appleton, B
Abstract : Acute necrotising encephalopathy (ANE) is a rare encephalitis-like syndrome usually reported in East Asia. This clinical syndrome tends to be triggered by viral febrile illness with rapid deterioration to seizures, coma and a generally poor outcome. Diagnosis is usually made on MRI. Its epidemiology is unknown largely due to under-recognition. Recurrent ANE has recently been associated with a newly discovered autosomal dominant mutation Ran binding protein 2. There had been reports encouraging the use of empirical corticosteroids as treatment for this condition. However, there have not been any clinical trials to date. Here we report an unusual case of a Caucasian toddler who had suffered two episodes of ANE, but did not receive any specific treatment and has normal physical and cognitive outcome at 1 year follow up. He has this missense mutation Ran binding protein 2 as have his mother and brother who are both well. This case adds to the worldwide literature and expands on the spectrum of this condition. The authors therefore propose that there should be a multi-centre controlled trial, before empirical use of corticosteroid could be advocated.